Religious Moderation Based on Local Culture in The Kusu Tidore Island Community - Marasabessy, Abd. Chaidir; Siagian, Amrizal (Universitas Pendidikan Ganesha, 2025)
The Kusu Tidore community is characterised by a high degree of diversity, which is generally regarded as a positive asset. However, this diversity can also give rise to tensions between different groups. The objective of this paper is to provide a comprehensive description of the phenomenon of religious moderation within the Kusu Tidore community, with a focus on its deep-rootedness in the local cultural context. In addition, the paper seeks to undertake a thorough analysis of the values and meanings associated with religious moderation. The present study employs a qualitative methodology, utilising scientific journals, books, and relevant documentation as data sources. In analysing the data, the author employs a predetermined formula for classification, subsequently processing the data and citing various literatures. This approach is intended to present research findings in a comprehensive and valid manner, by means of abstracting and discussing them to produce knowledge that underlies the conclusion of the study. The findings yielded the following conclusions: 1) The tradition of 'mejapanjang' in the Kusu community of Tidore Islands functions as a means of fostering amity between religious communities, thereby serving as a reflection of the majority group's role in providing protection to minority groups. The Tulude is a form of harmony, peace, and safety among the people of Halmahera. The Babari (bapalos) and Tulude (menulude) have a universal meaning that teaches tolerance, mutual cooperation, and assistance, as well as harmony and unity. These concepts are symbols of the Kusu community's culture and religious attitudes. Furthermore, the significance of 'Babari' (bapalos) and 'Tulude' lies in their role as the cornerstones of a paradigm and the social ethos of religion. These concepts emphasise the principle of deliberation and underscore the value of social justice within the local community. This study makes a significant contribution to the ongoing discourse on the threat of modernisation (socio-cultural change) to the preservation of local values in traditional communities. These local values become a source of motivation for the next generation and act as a solution to the cultural differences (custom) of the three tribes in the Kusu-Tidore community.